Hardness of composite resin polymerized with different light-curing units - Hengameh Safarcherati; Homayoun Alaghehmand (Babol University of Medical Sciences, 2012)
Introduction: The degree of polymerization depends on the type of light-curing unit. The aim of this study was to compare the hardness of composite resin cured by LED and Halogen light curing units. Methods: In this experimental study, 20 cylindrical samples of Tetric Ceram composite were prepared. Half of them were cured with Ultralume 2 LED and the other half with Astralis 7 Halogen light curing unit. In the depths of 0,1,2 and 3 mm from surface, one point in peripheral and one point in central portion were marked ,then the hardness of these points was measured by Vickers test . The data was analyzed by a pvalue less than 0.05 considered as significant. Results: The mean hardness of samples cured by LED was more than halogen group in different depths and this difference was statistically significant in peripheral points (p=.048) but this was not significant in central points (p=0.644). The mean hardness in both groups had a decreasing trend from surface to the deep parts in central and peripheral parts and this was more in the central parts. Conclusions: Composites cured by LED light curing unit showed more hardness in similar depths, besides the hardness of composites in central parts is more than the peripheral ones in both groups.